2022
DOI: 10.1111/ejh.13827
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year longitudinal analysis of hydroxyurea implementation in a pediatric sickle cell program

Abstract: Hydroxyurea (HU) has proven benefit in sickle cell anemia (SCA), but HU is still underutilized. The Pediatric Sickle Cell Program of Northern Virginia prescribes HU regardless of symptoms to all SCA patients age ≥ 9 months and prospectively tracks outcomes. HU is dosed to maximum tolerated dosing (MTD), targeting 30% Hgb F. Longitudinal data from 2009 to 2019 encompassing 1222 HU‐eligible and 950 HU‐exposure patient‐years were analyzed in 2‐year intervals for hemoglobin (Hgb), fetal hemoglobin (Hgb F), hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Reported here is additional analysis of results from our previously published uniform HU implementation program, 1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported here is additional analysis of results from our previously published uniform HU implementation program, 1…”
Section: Discussionmentioning
confidence: 99%
“…The Northern Virginia study reported on all patients in the program with SCA regardless of insurance coverage, thus raising the question of whether the high HU usage rate achieved in this program was influenced by a high proportion of non‐Medicaid patients or other unusual demographic features. Therefore, we analyzed our previously reported HU usage data 1 by insurance, ethnicity, and age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a community‐based study where HU was given to infants >9 months old who were followed for at least 6 years, HbF rose from 13 ± 8.7% to 26 ± 9.9% while hospitalizations decreased from 0.7 to 0.2 admissions per person‐year, and the incidence of ACS decreased from 14.6 to 4.2 per 100 patients‐years 24 . By the last 2‐year interval of follow‐up, 72% of patients had total hemoglobin >9 g/dL, 42% had HbF >30%, 79% experienced no hospitalizations, and 94% received no transfusions 25 . Despite its benefits HU is not a “cure.” Dosing in adults is often a challenge because of poor adherence, a dearth of knowledgeable adult providers, myelotoxicity, and diminished bone marrow reserve 16,26–29 .…”
Section: Pathophysiology and A Pathophysiologic Approach To Treatmentmentioning
confidence: 98%
“…24 By the last 2-year interval of follow-up, 72% of patients had total hemoglobin >9 g/dL, 42% had HbF >30%, 79% experienced no hospitalizations, and 94% received no transfusions. 25 Despite its benefits HU is not a "cure." Dosing in adults is often a challenge because of poor adherence, a dearth of knowledgeable adult providers, myelotoxicity, and diminished bone marrow reserve.…”
Section: Hydroxyureamentioning
confidence: 99%